Burn scenario in a single North-Eastern State of India: A 5-year retrospective study - Samuel Lalruatfala Sailo; Saia Chenkual; Vanlalhlua Chawngthu; Richard Lalramhluna Chawngthu (Wolters Kluwer Medknow Publications, 2019)
Introduction: The exact figure of burn injuries is still unavailable in many states of India. Some northeast Indian states with their unique social structure, hilly terrain, and practice of shifting (Jhum) cultivation the pattern of burn injuries in these states may be different. Materials and Methods: The burn records between March 2012 and April 2017 were retrospectively studied from all the district and private hospitals of the state. The demographic profiles, etiologies, delay in admission, percentage, and degrees of burn, hospital days, managements, and outcome on a single hill state of India were reviewed and analyzed. Results and Observations: The total number of patients studied was 450 with a mean age of 18.94 years. There were 281 male (62.4%), 168 female (37.3%), and one missing sex data, out of which 17 (4.2%) expired. Majority of the admission were in the winter season. The most common etiology was scald burn (55%). Suicidal intent was recorded in 8 patients (1.8%). The mean percentage of burn was 21.72%. Conclusion: The pattern of burn cases in the state showed marked variance from studies of other larger states of the country. Lifestyle modification, improving living standard, and active NGO participation seem to influence the low incidence of burn in the state.